Transmission constrained maintenance scheduling of generating units: a stochastic programming approach - Silva, E.L.; Morozowski, M.; Fonseca, L.G.S.; Oliveira, G.C.; Melo, A.C.G.; Mello, J.C.O. (IEEE transactions on power systems, 1995)
This paper presents a new methodology for maintenance scheduling that takes into account inter-area transfer limitations and stochastic reliability constraints. The optimization model is based on the Benders decomposition technique. The objective of this model is to determine a minimum cost maintenance schedule, subject to technological and system reliability constraints. The model may also be used to assess the adequacy of existing transmission limits under a given set of planned outages of generating units. Case studies with a realistic three-area power system are presented and discussed.< >